In-process mechanical working of additive manufactured Rene 41 - James, William Sean; Ganguly, Supriyo; Pardal, Goncalo (American Society of Mechanical Engineers (ASME), 2023)
In developing the wire + arc additive manufacturing (WAAM) process for creep resistant alloys for defence applications, structures were built from nickel-based superalloy Rene 41 (RE41). The performance of the additive manufactured alloy was analysed for applications including components used in high-speed flight environments, where external structures could reach service temperatures of up to 1000 K. As a single use system with relatively short flight times of < 1 hour, components will be highly stressed to minimise structural mass. In this paper, three wall structures were deposited using a plasma transferred arc process, in a layer-by-layer manner where each layer was mechanically worked by machine hammer peening directly after deposition. With a constant impact frequency, three different travel speeds for the peening tool were used for each wall structure. To understand the most effective cold working parameters, samples were tested and analysed for their mechanical properties and microstructural characteristics after aging treatment. Samples were tested at room temperature and compared with results of both non-worked heat-treated AM material and wrought data obtained from literature review.